ANALISIS RASIO LIKUIDITAS, RENTABILITAS, SOIVABILITAS PADA KINERJA KEUANGAN BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ferlina Halawa; Erni Yanti Natalia (SCIENTIA JOURNAL, 2022)
This study aims to determine the financiaI performance of banks Iisted on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. This study consists of variabIes Current Ratio (X1), Net Profit Margin (X2), Debt to Equity Ratio (X3) on Return On Assets (Y). Based on the resuIts of the study it was concIuded that partiaIIy the Current Ratio (X1) and Debt to Equity Ratio (X3) variabIes showed a significant effect on Return On Assets (Y), whiIe the Net Profit variabIe Margin (X2) partiaIIy shows no effect on Return On Assets (Y), but together the variabIes Current Ratio (X1), Net Profit Margin (X2), Debt to Equity Ratio (X3) show an effect on Return On Assets ( Y. The coefficient of determination of 22.9% indicates that the VariabIe Current Ratio (X1), Net Profit Margin (X2), Debt to Equity Ratio (X3) onIy affect 22.9% on Return On Assets (Y) and the remaining 77 ,1% infIuenced by other variabIes that were not examined in this study.